2019
DOI: 10.1111/apt.15382
|View full text |Cite
|
Sign up to set email alerts
|

Letter: tenofovir disoproxil fumarate is safe for prevention of mother‐to‐child transmission of hepatitis B virus. Authors’ reply

Abstract: Linked ContentThis article is linked to Wang et al and Fan et al papers. To view these articles, visit https://doi.org/10.1111/apt.15064 and https://doi.org/10.1111/apt.15305.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…There is discrepancy among guidelines, which rose in the contexts of fewer safety data at the second-trimester treatment of TDF in RCTs, and the necessity of starting TDF earlier than the third trimester for PMTCT at the time of preparing the guidelines. Recently a large real-world study suggested that providing TDF at the second trimester could be more effective in controlling viremia than that in the third trimester [49,50] . In a viral kinetic study by Pan et al, treatment with 24 weeks of TDF was more effective (97%) in reducing HBV DNA levels to < 200,000 IU/ml versus 12 weeks of TDF therapy (94%) in reproductive-age women [51] .…”
Section: Discussion Of Current Challenges Possible Solutions and Rese...mentioning
confidence: 99%
“…There is discrepancy among guidelines, which rose in the contexts of fewer safety data at the second-trimester treatment of TDF in RCTs, and the necessity of starting TDF earlier than the third trimester for PMTCT at the time of preparing the guidelines. Recently a large real-world study suggested that providing TDF at the second trimester could be more effective in controlling viremia than that in the third trimester [49,50] . In a viral kinetic study by Pan et al, treatment with 24 weeks of TDF was more effective (97%) in reducing HBV DNA levels to < 200,000 IU/ml versus 12 weeks of TDF therapy (94%) in reproductive-age women [51] .…”
Section: Discussion Of Current Challenges Possible Solutions and Rese...mentioning
confidence: 99%
“…[15,44,53,54] Preliminary data from the TA PROHM study demonstrating that tenofovir with full schedule HBV vaccination alone may be similarly effective to hepatitis B immune globulin plus tenofovir and full schedule HBV vaccination for prevention of mother-to-child HBV transmission are encouraging [55] though further studies are needed before widespread adoption of this strategy. Tenofovir alafenamide has a higher safety profile than tenofovir disoproxil fumarate (including in pregnancy), would be preferable to tenofovir to reduce adverse event monitoring requirements and costs, [56] however, remains unaffordable in most countries, and is not yet included in WHO guidelines.…”
Section: Implementation Of Hbv Cure: What Is Requiredmentioning
confidence: 99%